Filler Composition Effects on Tensile Strength And Composite Material Toughness of Rice-Resin Husk Powder - Istiroyah Istiroyah; L. Nuriyah; Retnowati Retnowati (Natural B, Journal of Health and Environmental Sciences, 2012)
The rice husk flour- resincomposite has been made. This research aims to make the rice husk flour - resin composite and analyze the effect of filler composition to their tensile strength and toughness. The filler composition used is 0%, 10%, 20%, 30, 40%, 50% dan 60%. The Results of tensile test show that the best tensile strength is 113.02 ±11.60 MPa for polystiren sample. The best toughness with impact test is 47.92±0,36 KJ/m2 for 30% filler with polyester resin.